2013
DOI: 10.1002/lsm.22147
|View full text |Cite
|
Sign up to set email alerts
|

Imaging and characterization of bioengineered blood vessels within a bioreactor using free‐space and catheter‐based OCT

Abstract: This study suggests that combination of free-space and catheter-based OCT for blood vessel imaging provides accurate structural information of the developing blood vessel. We determined that free-space OCT images could be co-registered with catheter-based OCT images to monitor structural features such as wall thickness or delamination of the developing tissue-engineered blood vessel within a bioreactor. Structural parameters and optical properties obtained from OCT imaging correlate with histological sections … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…We recently demonstrated the ability of OCT to image a developing tissue-engineered blood vessel within a bioreactor using either free-space OCT imaging or a vascular OCT endoscope. 19 We were able to observe changes in the wall thickness and optical properties of the vessel over 4 weeks. However, one of the major limitations of OCT is its inability to extract cellular and molecular signatures specifically and sensitively.…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…We recently demonstrated the ability of OCT to image a developing tissue-engineered blood vessel within a bioreactor using either free-space OCT imaging or a vascular OCT endoscope. 19 We were able to observe changes in the wall thickness and optical properties of the vessel over 4 weeks. However, one of the major limitations of OCT is its inability to extract cellular and molecular signatures specifically and sensitively.…”
Section: Introductionmentioning
confidence: 91%
“…Control images of the same regions were also obtained with the Leica fluorescence microscope. The media was replaced every 24 h. A tubular bioreactor as described earlier 19 was used for EC imaging of tubular PDLLA scaffolds. Short segments (*1 cm) of thin fluorinated ethylene propylene (FEP) tube (OD = 3 mm) were glued to the two ends of the PDLLA scaffolds using medical-grade silicone adhesive (Silastic medical adhesive type A; Dow Corning Corp.).…”
Section: Cell Culture and Cell Seedingmentioning
confidence: 99%
See 1 more Smart Citation
“…MRI can provide cellular-level imaging with the proper labeling but is limited by depth of penetration and the unknown effect of labeling agents [78]. Optical coherence tomography can provide information about ECM changes in vascular graft but is limited in resolution [81]. Optical imaging techniques, including multiphoton imaging [82], two photon and confocal microscopy, have the potential to monitor individual fluorescently labeled cells [83]; however, these techniques have a limited penetration depth, which limits their application in TEBV monitoring.…”
Section: Tebv Assessmentmentioning
confidence: 99%
“…44 A vessel catheter with optical coherence tomography has been constructed for accurate evaluation of structural information from developing vessels. 40 In a further study, 18 F-ZW-104, a novel positron emission tomography radioligand, was developed to display central nicotinic acetylcholine receptors in baboons, 59 and the results indicated that this new radioligand could be used in humans to study nicotinic acetylcholine receptors containing the β2 subunit. Further, in a study by Muller et al, 47 a novel optical high resolution system was developed to display adult cardiomyocytes.…”
mentioning
confidence: 99%